La Psicosis: Un Estudio Desde La Subjetividad - Arroyo, JosÃ© Manuel GarcÃa (European Scientific Journal, ESJ, 2017)
In psychiatry the definition of psychosis has been sustained in the symptoms, without attending practically to the person who suffers them. This phenomenon has intensified since the appearance of the Diagnostic Manuals. In this article we consider psychosis as a "structure", with defined characteristics, and according to this, we will determine which its subjective keys are. To achieve this, we rely on a strategy that allows the study of "interiority" and makes it scientific. The result is a new way of understanding psychosis, so that the classic idea that the psychotic is a person "enclosed in itself" and "incapable of being objective" is destroyed. On the contrary, it is demonstrated a "subjective collapse" that prevents him from having "internal" formations (fantasies, desires, projects, schemes of life, and so on) and keeps him prisoner of the exterior. This explains the lack of sense of the phenomena that he suffers and the absence of insertion in the culture.